AN EXPERIMENTAL STUDY TO PRODUCE FISH FODDER USING ALTERNATIVE INGREDIENTS - Yuniarti, Rahmi; Efranto, Remba Yanuar; Azlia, Wifqi; Oktavianty, Oke; Mohamad, Effendi (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2021)
The sustainable and economic development of the fishing industry is heavily dependent upon the choice of raw materials used in fish fodder. Furthermore, an inappropriate amount or nutritional quality of fodder will impede the health and growth of the farmed fish. This work therefore aims to determine the feasibility of substituting snail flour for fishmeal in fodder. The experimental and statistical results indicated no significant nutritional difference between fodder synthesized with fishmeal or snail flour as the protein source. Therefore, snail flour can be used to replace fishmeal used in milkfish fodder without negatively affecting the health of the milkfish.